Low-mass eclipsing binaries in the WFCAM Transit Survey: the persistence of the M-dwarf radius inflation problem - Cruz, P; Diaz, M; Birkby, J; Barrado, D; Sipöcz, B; Hodgkin, S (Oxford University Press, 2018)
We present the characterization of five new short-period low-mass eclipsing binaries (LMEBs) from the WFCAM Transit Survey. The analysis was performed by using the photometric WFCAM J-mag data and additional low- and intermediate-resolution spectroscopic data to obtain both orbital and physical properties of the studied sample. The light curves and the measured radial velocity curves were modelled simultaneously with the JKTEBOP code, with Markov chain Monte Carlo simulations for the error estimates. The best-model fit have revealed that the investigated detached binaries are in very close orbits, with orbital separations of 2.9 ≤ a ≤ 6.7 R⊙ and short periods of 0.59 ≤ Porb ≤ 1.72 d, approximately. We have derived stellar masses between 0.24 and 0.72 M⊙ and radii ranging from 0.42 to 0.67 R⊙. The great majority of the LMEBs in our sample has an estimated radius far from the predicted values according to evolutionary models. The components with derived masses of M < 0.6 M⊙ present a radius inflation of ∼9 per cent or more. This general behaviour follows the trend of inflation for partially radiative stars proposed previously. These systems add to the increasing sample of low-mass stellar radii that are not well-reproduced by stellar models. They further highlight the need to understand the magnetic activity and physical state of small stars. Missions like TESS will provide many such systems to perform high-precision radius measurements to tightly constrain low-mass stellar evolution models.